Patient satisfaction with community clinic care: facility and household based survey in a sub-district in Bangladesh - Ferdousi, Mst Jannatul (Mediscope, 2015)
Bangladesh government has initiated a project with the title of "Revitalization of Community Health Care Initiatives in Bangladesh (RCHCIB)" to further develop the Community Clinics (CCs) and strengthen their operations in delivering primary health care. Measuring patient satisfaction with CC service users can play an important role in developing quality care. The objectives of this study were to measure patient satisfaction with CC through facility (CC) based survey and to measure overall patient satisfaction with CC through household based survey. The overall mean patient satisfaction score was 3.7 ± 1.0 and 2.4 ± 1.1 for facility based survey and household based survey, respectively. Policy and strategy should be done to increase quality of care resulting high level of patient satisfaction to service provided at CCs. DOI: http://dx.doi.org/10.3329/mediscope.v1i1.21633 Mediscope Vol. 1, No. 1: 2014, Pages 23-28